Sediment yield modelling for small agricultural catchments: land-cover parameterization based on remote sensing data analysis - Paringit, Enrico C.; Nadaoka, Kazuo (Hydrological processes, 2003)
Vegetation and soil properties and their associated changes through time and space affect the various stages of soil erosion. The island of Ishigaki in Okinawa Prefecture, Japan is of particular concern because of the propensity of the red‐soil‐dominated watersheds in the area to contribute substantial sediment discharge to adjacent coastal areas. This paper discusses the application of remote sensing techniques in the retrieval of vegetation and soil parameters necessary for the distributed soil‐loss modelling in small agricultural catchments and analyses the variation in erosional patterns and sediment distribution during rainfall events using numerical solutions of overland flow simulations and sediment continuity equations. To account for the spatial as well as temporal variability of selected parameters of the soil‐loss equations, a method is proposed to account for the variability of associated vegetation cover based on their spectral characteristics as captured by remotely sensed data. To allow for complete spatial integration, modelling the movement of sediment is accomplished under a loose‐coupled GIS computational framework. This study lends a theoretical support and empirical evidence to the role of vegetation as a potential agent for soil erosion control. Copyright © 2003 John Wiley & Sons, Ltd.